2020
DOI: 10.14336/ad.2019.1104
|View full text |Cite
|
Sign up to set email alerts
|

Chondroprotective Effects of Combination Therapy of Acupotomy and Human Adipose Mesenchymal Stem Cells in Knee Osteoarthritis Rabbits via the GSK3β-Cyclin D1-CDK4/CDK6 Signaling Pathway

Abstract: Adipose-derived stem cells (ASCs) are highly chondrogenic and can be used to treat knee osteoarthritis (KOA) by alleviating cartilage defects. Acupotomy, a biomechanical therapy guided by traditional Chinese medicine theory, alleviates cartilage degradation and is widely used in the clinic to treat KOA by correcting abnormal mechanics. However, whether combining acupotomy with ASCs will reverse cartilage degeneration by promoting chondrocyte proliferation in KOA rabbits is unknown. The present study aimed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 82 publications
(94 reference statements)
1
14
0
Order By: Relevance
“…However, whether acupotomy as biomechanical therapy is sufficient to prevent or reverse KOA-induced subchondral bone lesions has not been directly investigated. e biomechanical effects of acupotomy have been confirmed in our preliminary studies [21][22][23][24]. It is well known that muscle dysfunction, characterized by weakened muscle strength and reduced coordination of muscle groups, is a crucial cause of KOA knee mechanical imbalance [37].…”
supporting
confidence: 62%
See 3 more Smart Citations
“…However, whether acupotomy as biomechanical therapy is sufficient to prevent or reverse KOA-induced subchondral bone lesions has not been directly investigated. e biomechanical effects of acupotomy have been confirmed in our preliminary studies [21][22][23][24]. It is well known that muscle dysfunction, characterized by weakened muscle strength and reduced coordination of muscle groups, is a crucial cause of KOA knee mechanical imbalance [37].…”
supporting
confidence: 62%
“…e biomechanical effect of acupotomy is the unique superiority that distinguishes it from other KOA therapies. Preliminary studies [21][22][23][24] have confirmed that acupotomy can prevent cartilage degeneration and delay KOA pathological procession by correcting the abnormal mechanical stress in KOA joints. Is the chondroprotective effect of acupotomy related to the inhibition of KOA subchondral bone resorption?…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rabbit model of cartilage degeneration in KOA was reproduced by plaster immobilization in the right hind limb extension position for 6 weeks [ 25 , 26 ], and the operation is performed as in Figure 1(c) . The rabbit was simply placed in a supine position on the immobilizer, exposing the right knee joint.…”
Section: Methodsmentioning
confidence: 99%